A patient reported outcome measure in homeopathic clinical practice for long-term conditions. Issue 4 (November 2016) - Thompson, Elizabeth; Viksveen, Petter; Barron, Susan
Abstract : Background: This study was initiated as part of a quality improvement audit process to create standards around goal setting with our patients to understand and improve outcomes of homeopathic treatment. Method: We used the Measure Yourself Medical Outcome Profile (MYMOP2) as a tool to assist clinicians in setting the treatment goals across a wide range of diagnoses and other complaints in routine clinical practice at the Bristol Homeopathic Hospital. The data collected from the MYMOP2 is of significance in its own right and the results are now reported in this paper. Results: A total of 198 patients with a wide range of complaints attended one to five consultations with 20 homeopathic doctors. Diagnostic categories were most commonly neoplasms (16.7%), psychological (13.9%) and genitourinary complaints (12.3%), with 66.7% suffering from these problems for at least one year. The three symptoms that bothered patients the most were pain, mental symptoms and tiredness/fatigue. A paired-samples t-test using an intention-to-treat analysis showed that the MYMOP2 profile score improved from 4.25 (IQR 3.50–5.00), with a mean change of 1.24 (95% CI 1.04, 1.44) from the first to the last consultation (p < 0.001). Results were statistically significant both for completers (n = 91) (p < 0.001) and non-completers (n = 107) (p < 0.001) using last-observation-carried-forward, although completers did better than non-completers (p < 0.001). The overall clinical significance of improvements was at least moderate. A repeated measures ANOVA test also showed statistically significant improvements (p < 0.001). Conclusion: The MYMOP2 results add to a growing body of observational data which demonstrates that when patients with long term conditions come under homeopathic care their presenting symptoms and wellbeing often improve. Offering a low cost high impact intervention to extend the range of choice to patients and to support self-care could be an important part of the NHS.